Resistant and refractory hypertension: two sides of the same disease? - Elizabeth Silaid Muxfeldt; Bernardo Chedier; Cibele Isaac Saad Rodrigues (Brazilian Journal of Nephrology, 2018)
Abstract Refractory hypertension (RfH) is an extreme phenotype of resistant hypertension (RH), being considered an uncontrolled blood pressure besides the use of 5 or more antihypertensive medications, including a long-acting thiazide diuretic and a mineralocorticoid antagonist. RH is common, with 10-20% of the general hypertensives, and its associated with renin angiotensin aldosterone system hyperactivity and excess fluid retention. RfH comprises 5-8% of the RH and seems to be influenced by increased sympathetic activity. RH patients are older and more obese than general hypertensives. It is strongly associated with diabetes, obstructive sleep apnea, and hyperaldosteronism status. RfH is more frequent in women, younger patients and Afro-americans compared to RFs. Both are associated with increased albuminuria, left ventricular hypertrophy, chronic kidney diseases, stroke, and cardiovascular diseases. The magnitude of the white-coat effect seems to be higher among RH patients. Intensification of diuretic therapy is indicated in RH, while in RfH, therapy failure imposes new treatment alternatives such as the use of sympatholytic therapies. In conclusion, both RH and RfH constitute challenges in clinical practice and should be addressed as distinct clinical entities by trained professionals who are capable to identify comorbidities and provide specific, diversified, and individualized treatment.